PERILAKU BERKENDARA SEPEDA MOTOR 150 CC MENGGUNAKAN METODE NATURALISTIC DRIVING STUDY DAN DRIVERS BEHAVIOUR QUESTIONNAIRE - Suaib, Fadel; Lahay, Idham Halid; Wolok, Eduart (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
Driver behavior is the most dominant factor in accidents. Almost all accidents are preceded by violations of traffic signs. Through previous accident data, important and useful information can be known. The study aims to analyze two-wheeled motorbike riding behavior using Naturalistic Driving Study (NDS) and determine the influence of age and behavior of 150cc motorbike riders. Data taken from recordings taken by respondents and questionnaires. The results of the regression test to determine differences in age on motorbike rider behavior with a constant value of a = 196.03 show that this figure is a constant number which means that, if it does not involve age (X), the value of riding behavior (Y) is -5, 3956x. The regression coefficient is -5.3945. This figure is minus (-), which means that age (X) has a negative effect on driving behavior (Y).